Adsorptive removal of some Cl-VOC's as dangerous environmental pollutants using feather-like γ-Al2O3 derived from aluminium waste with life cycle analysis. (May 2022) - Halawy, Samih A.; Osman, Ahmed I.; Mehta, Neha; Abdelkader, Adel; Vo, Dai-Viet N.; Rooney, David W.
Abstract: Herein, we designed a cost-effective preparation method of nanocomposite γ-Al2 O3 derived from Al-waste. The produced material has a feather-like morphology, and its adsorption of some chlorinated volatile organic compounds (Cl-VOC's) such as benzyl chloride, chloroform and carbon tetrachloride (C7 H7 Cl, CHCl3 and CCl4 ) was investigated due to their potential carcinogenic effect on humans. It showed a characteristic efficiency towards the adsorptive removal of these compounds over a long period, i.e., eight continuous weeks, at ambient temperature and atmospheric pressure. After 8-weeks, the adsorbed amounts of these compounds were determined as: 325.3 mg C7 H7 Cl, 247.6 mg CHCl3 and 253.3 mg CCl4 per g of γ-Al2 O3, respectively. CCl4 was also found to be dissociatively adsorbed on the surface of γ-Al2 O3, whereas CHCl3 and C7 H7 Cl were found to be associatively adsorbed. The prepared γ-Al2 O3 has a relatively high surface area (i.e., 192.2 m 2 . g −1 ) and mesoporosity with different pore diameters in the range of 25–47 Å. Furthermore, environmental impacts of the nanocomposite γ-Al2 O3 preparation were evaluated using life cycle assessment. For prepartion of adsorbent utilising 1 kg of scrap aluminium wire, it was observed that potential energy demand was 288 MJ, climate change potential was 19 kg CO2  equivalent, acidification potential was 0.115 kg SO2  equivalent and eutrophication potential was 0.018 kg PO4 3−  equivalent. Graphical abstract: Image 1 Highlights: The first detailed scientific study in the adsorptive removal of C7 H7 Cl. γ-Al2 O3 showed superior adsorption capacity after 8-weeks adsorption of Cl–VOCs. C7 H7 Cl and CHCl3 associatively adsorb over γ-Al2 O3 but CCl4 dissociatively adsorbed. Environmental impacts of γ-Al2 O3 preparation evaluation via life cycle assessment.